Henkilöstöpolitiikan haasteet monikulttuurisessa organisaatiossa : United Nations assistance mission in Afghanistan 2015 - Rantanen, Mauno (2016)
The main objective of this thesis was to isolate the challenges related on the human resource (HR) and staffing policies in the multicultural organization and what sort of positive output it will have on the organization employees if any. The purpose of the study was to examine various HR policy options available, and based on that senior management of the organization would have better view on what sort of HR policies and staff development plans should be emphasized in the organization. The purpose of the policy planning is to support the organization structure and to maximize the staff-ing performance at the workplace throughout the various professional trainings and career development plans.